1-(4-Bromophenyl)-3-chloropropan-1-one - Marcel Sonneck; Anke Spannenberg; Sebastian Wohlrab; Tim Peppel (IUCrData)
The title compound, C9H8BrClO, crystallizes in the monoclinic space group P21/n with four molecules in the unit cell. The molecular structure consists of almost planar molecules with the chlorine atom protruding from this plane.